PENINGKATAN KINERJA DAN KESELAMATAN PERSIMPANGAN DI KAWASAN PUSAT KOTA MALANG - Imma Widyawati Agustin (Jurnal Pengembangan Kota, 2016)
The needs of transportation is increasing following the urban area development. When the transport demands is higher than available transport infrastructure, the effect will be some problem such as traffic jam, accident, delay, noise and air pollution. The main purpose of the research is to improve the performance and the safety level of intersection in the city centre of Malang. The research used street performance analysis based on Indonesian Highway Capasity Manual with three steps: first, analyzing street intersection’s performance for the existing condition and the next five years. Second, compared street and intersection’s performance with the standard that has occured. Third, analyzed the performance of street and intersection after application of traffic management. The result showed that appropriate traffic management to be applied in Basuki Rahmat Street  is alternative 1 of the demand management, such as the application of one way system for the whole segments and it equipped by public transport lanes which can increase the level of service of the whole segments in Basuki Rahmat Street, as well as meet the level of service that has been ideal for the secondary arterial roads.